Organizational Culture : Employee Perception of PT. Indomarco Prismatama - Dian Juliarti Bantam; Muhammad Pratama Ardin; Najwa Shafira; Miftakul Janah (Eduvest - Journal of Universal Studies, 2024)
This study discusses the employees' perceptions of the organizational culture at PT. Indomarco Prismatama. Through a qualitative approach, this research highlights aspects such as the business environment, values, role models, rituals, and networking within the organization, as outlined by Deal and Kennedy (Bantam, Nugraha, & Sa’adah, 2016). The research method employed is phenomenology to understand employees' experiences related to work culture. The research findings indicate that collaboration, support, honesty, integrity, and discipline are important values applied within the company. Additionally, role models such as district business managers set motivating examples for employees. Company rituals and informal communication networks also play a role in strengthening the organizational culture. In conclusion, a positive organizational culture plays a key role in achieving common goals and maintaining a productive work environment.